2019
DOI: 10.21668/health.risk/2019.2.04
|View full text |Cite
|
Sign up to set email alerts
|

Hygienic assessment of population health risks caused by combined oral introduction of heavy metals

Abstract: Проблема комбинированного перорального поступления тяжелых металлов с питьевой водой и пищевыми продуктами в организм человека является актуальной. Это связано с контаминацией продуктов, с большой вероятностью миграции металлов в воду и растения из почвы, атмосферного воздуха и т.п. Целью научного исследования явилась гигиеническая оценка комбинированного перорального поступления тяжелых металлов с питьевой водой и продуктами питания с последующей оценкой риска для здоровья населения. В работе проанализированы… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
0
0
Order By: Relevance
“…V.M. Boev et al found that HQ was at the permissible level for intake of individual contaminants, as well as HI for combined intake of lead, cadmium, arsenic and mercury with food in median concentrations and in the 90th percentile [18]. Research conducted by A.G. Setko et al assessed non-carcinogenic risk and demonstrated that the level of risk was at an acceptable level (HQ ≤ 1) for main contaminants (nitrates, mercury, arsenic, cadmium) between 2007 and 2015 [19].…”
Section: T a B L Ementioning
confidence: 99%
See 2 more Smart Citations
“…V.M. Boev et al found that HQ was at the permissible level for intake of individual contaminants, as well as HI for combined intake of lead, cadmium, arsenic and mercury with food in median concentrations and in the 90th percentile [18]. Research conducted by A.G. Setko et al assessed non-carcinogenic risk and demonstrated that the level of risk was at an acceptable level (HQ ≤ 1) for main contaminants (nitrates, mercury, arsenic, cadmium) between 2007 and 2015 [19].…”
Section: T a B L Ementioning
confidence: 99%
“…Analysis of literature on food contamination with heavy metals has shown that studies of risk are often based on data from the Federal State Statistics Service on average annual per capita consumption of the main groups of food products, which indicate regional peculiarities of risk formation. Thus, results of assessment of exposure to heavy metals in the Orenburg region on the basis of average per capita food consumption showed that milk and dairy products ranked first in terms of contributions to total exposure to lead, cadmium and arsenic; vegetables and gourds ranked second and third in terms of contributions to total exposure to lead, cadmium and arsenic; bread products, vegetables and gourds ranked first in terms of contributions to total mercury exposure, bread products ranked second, milk and dairy products ranked third [18]. Assessment of non-carcinogenic risks to health of the population of 16 districts of the Republic of Bashkortostan from contamination with lead, cadmium, chromium, nickel, copper, and zinc revealed 3 districts with high risk values (HI = 1.01-1.34) due to consumption of vegetable crops by the population of these districts [20].…”
Section: T a B L Ementioning
confidence: 99%
See 1 more Smart Citation